Evaluation of the Variability and Frequency of Infectious Diseases in the Ngorongoro Conservation Area, Ngorongoro District in Arusha Region, Tanzania - O. F. Linuma; A. S. Mahenge; R. R. A. M. Mato; A. D. Greenood (Journal of Applied Sciences and Environmental Management, 2024)
The Ngorongoro Conservation Area (NCA) frequently experiences the emergence and re-emergence of infectious diseases. However, it is unclear how emergence varies or changes in frequency. Hence, the objective of this was to evaluate the Variability and frequency of infectious diseases in the Ngorongoro Conservation Area, Ngorongoro district in the Arusha region of Tanzania using appropriate standard methods such as questionnaire surveys, field visits, documentation reviews, and focus group discussions. A total of 396 households participated in the survey from four selected villages, Nainokanoka, Endulen, Kayapus, and Meshili, within the NCA. The collected responses were analysed to determine physical and cultural practices potentially influencing the variability and frequency of infectious diseases. The results suggest a combination of environmental factors, cultural practices, and wildlife conservation measures influence the variability and frequency of infectious diseases in the study including climatic conditions, meat consumption, and scarcity of suitable land for pasture, the presence of wildlife corridors, large livestock numbers and lack of hygiene. Diseases frequently reported to occur were Anthrax, Tuberculosis, Brucellosis, Rabies, Malignant catarrhal fever (MCF), and Malaria. Mitigating pathogens transmission risk will require mapping high-risk areas precisely and public education initiatives to minimize contact between pathogens and the populace within the study area.